2016
DOI: 10.1080/19491034.2016.1260802
|View full text |Cite
|
Sign up to set email alerts
|

SUN1 splice variants, SUN1_888, SUN1_785, and predominant SUN1_916, variably function in directional cell migration

Abstract: The LINC complex is a multifunctional protein complex that is involved in various processes at the nuclear envelope, such as nuclear migration, mechanotransduction and chromatin tethering in the meiotic phase. However, it remains unknown how these functions are regulated in different cell contexts. An inner nuclear membrane component of the LINC complex, SUN1, is ubiquitously expressed. The human SUN1 gene produces over 10 variants by alternative splicing. Although functions of SUN1 are relatively well charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 50 publications
2
81
0
Order By: Relevance
“…Moreover, SUN1–SUN2 heterotrimer formation is feasible for the following two reasons. First, biochemical analyses have shown that SUN1 and SUN2 can form a hetero-oligomer [11,28,49,55,56,57], and second, the molecular organization of SUN 1 and SUN2, such as the length of the coiled-coil domains or the SUN domain, is similar. Thus, four kinds of SUN protein trimers are possible (Figure 2B).…”
Section: Compositional Nature Of the Sun–kash Hetero-hexamermentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, SUN1–SUN2 heterotrimer formation is feasible for the following two reasons. First, biochemical analyses have shown that SUN1 and SUN2 can form a hetero-oligomer [11,28,49,55,56,57], and second, the molecular organization of SUN 1 and SUN2, such as the length of the coiled-coil domains or the SUN domain, is similar. Thus, four kinds of SUN protein trimers are possible (Figure 2B).…”
Section: Compositional Nature Of the Sun–kash Hetero-hexamermentioning
confidence: 99%
“…Likewise, SUN1 may exist in dimers or tetramers, not trimers in cells under some circumstances [55]. In addition, since each gene encoding SUN and nesprin proteins produces a wide range of splicing variants, and the expression level of variant proteins is tissue-dependent, the compositional nature of SUN–KASH hexamers significantly varies among tissues [10,11,12,21,28,58]. …”
Section: Compositional Nature Of the Sun–kash Hetero-hexamermentioning
confidence: 99%
See 3 more Smart Citations